2023
DOI: 10.1021/acsnano.3c04344
|View full text |Cite
|
Sign up to set email alerts
|

Translational Selenium Nanoparticles to Attenuate Allergic Dermatitis through Nrf2-Keap1-Driven Activation of Selenoproteins

Abstract: Easy recurrence and strong treatment side effects significantly limit the clinical treatment of allergic dermatitis. The human trace element selenium (Se) plays essential roles in redox regulation through incorporation into selenoproteins in the form of 21st necessary amino acid selenocysteine, to participates in the pathogenesis and intervention of chronic inflammatory diseases. Therefore, based on the safe and elemental properties of Se, we construct a facile-synthesis strategy for antiallergic selenium nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Fortunately, selenium (Se), an essential trace element involved in maintaining human health, was shown to have a mutual detoxification relationship with arsenic. A reliable detoxification mechanism in the body involves the reaction of arsenic and selenium in the liver, which accelerates their excretion in bile . Moreover, the intake of selenium at the nutritional level reduces cancer incidence by regulating immune functions through the diverse redox-regulating activities of selenoproteins, reversing the immunosuppression of the tumor microenvironment to promote an antitumor immune-activating status. Pioneering work by Chen et al on the development of Se-based therapy revealed the tremendous potential of Se in reprogramming the immune microenvironment of lung adenocarcinoma, generating vaccine nanoadjuvants, attenuating allergic dermatitis, recognizing metallodrugs, and reinvigorating cancer radioimmunotherapy. A promising combination of selenium and arsenic to form As 2 Se 3 could be an excellent strategy for lowering the toxic effects and increasing the therapeutic and immunomodulatory efficacy of arsenic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, selenium (Se), an essential trace element involved in maintaining human health, was shown to have a mutual detoxification relationship with arsenic. A reliable detoxification mechanism in the body involves the reaction of arsenic and selenium in the liver, which accelerates their excretion in bile . Moreover, the intake of selenium at the nutritional level reduces cancer incidence by regulating immune functions through the diverse redox-regulating activities of selenoproteins, reversing the immunosuppression of the tumor microenvironment to promote an antitumor immune-activating status. Pioneering work by Chen et al on the development of Se-based therapy revealed the tremendous potential of Se in reprogramming the immune microenvironment of lung adenocarcinoma, generating vaccine nanoadjuvants, attenuating allergic dermatitis, recognizing metallodrugs, and reinvigorating cancer radioimmunotherapy. A promising combination of selenium and arsenic to form As 2 Se 3 could be an excellent strategy for lowering the toxic effects and increasing the therapeutic and immunomodulatory efficacy of arsenic treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our observations indicated that LNT-functionalized SeNPs exhibited favorable attributes, including low cytotoxicity, efficient cellular uptake, and sustained stability [ 36 ]. Research from B. Xie et al suggests that, SeNPs@LNT can increase the Se content and selenoprotein expression in the skin, reduce mast cell activation and inflammatory cell infiltration, and thus demonstrate effective therapeutic effects in the study of allergic dermatitis [ 37 ]. Therefore, SeNPs@LNT may exhibit its antioxidant capacity and immune regulation by enhancing the activity of selenoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…5 Chen et al reported SeNPs encapsulated with lentinan (LET-SeNPs) can better attenuate allergic dermatitis than SeNPs through Nrf2-Keap1-driven activation of selenoproteins, suppress ROS-induced cyclooxygenase-2 (COX-2) and MAPKs activation to suppress the release of histamine and inflammatory cytokines. 6 They also use the polarization effect of the selenium atom to inhibit selenoprotein thioredoxin reductase (TrxR, which can cleave ROS) by constructing the electrophilic center −N−Se(δ + )−N−. 7 The hyaluronic acid modified selenium nanoparticle with a protective shell of calcium alginate (SA) hydrogel microbead mediated in situ synthesis of selenoproteins could prominently reduce proinflammatory cytokine secretion and mediate immune cells (e.g., reduce neutrophils and monocytes and increase immune regulatory T cells) to effectively relieve colitis-associated symptoms in comparison to SeNPs.…”
mentioning
confidence: 99%
“…They wrote in their comment, “The authors prepared selenium (Se) nanoparticles (NPs) by using human serum albumin (HSA) and suggested that the ‘HSA/Se NPs’ have lower toxicity and higher efficacy than other Se species. The other Se species employed in this article include Se yeast and previously reported SeNPs prepared by using bovine serum albumin (BSA), here referred to as BSA-SeNPs.” We believe that such a statement is inconsistent with the original text . The Abstract in the original text states: “Findings reveal that HSA/Se NPs have lower toxicity and higher efficacy than other selenium species and the ability to overcome the IEB and BBB to enrich DA neurons, which then protect MN9D cells from MPP + -induced neurotoxicity and ameliorate both behavioral deficits and DA neuronal death in MPTP-model mice” .…”
mentioning
confidence: 99%
See 1 more Smart Citation